Identification of PA28β as a potential novel biomarker in human esophageal squamous cell carcinoma - Jin-Yan Chen; Li Xu; Wei-Min Fang; Jun-Yong Han; Kun Wang; Kun-Shou Zhu (Tumor Biology)
Esophageal squamous cell carcinoma (ESCC) is one of the most common and serious malignancies in China. However, the exact mechanisms of tumor formation and progression are unclear. As late diagnosis and poor therapeutic efficacy result in lower survival rates, identifying biomarkers for early detection, prognostic evaluation, and recurrence monitoring of ESCC is necessary. Here we analyzed 10 protein expression profiles of ESCC core tissues and paired normal esophageal epithelial tissues using two-dimensional gel electrophoresis. We excised 29 protein spots with two-fold or greater differential expression between cancer and normal tissues and identified them using matrix-assisted laser desorption/ionization–time-of-flight/time-of-flight mass spectrometry. The role of PA28β in ESCC cell was confirmed using cell growth, colony formation and soft agar in TE-1 cells pre- and post- PA28β transfection. Compared to their expression in the adjacent normal epithelia, 12 proteins, including transgelin (TAGLN), were upregulated in ESCC tissues; 17 proteins, including proteasome activator 28-beta subunit (PA28β), were downregulated (p < 0.05). Western blotting and immunohistochemistry confirmed that PA28β was significantly underexpressed in ESCC tissues. The functional assays demonstrate that PA28β inhibited cell growth, proliferation and malignancy of TE-1 cells. Among the differentially expressed proteins, PA28β is a potential tumor inhibitor.